On the platonic concept of to metaxy: theory of perception and cultual experience - Rocha Rachid, Rodolfo José (Revista Archai, 2023)
In this paper I intend to examine the notion of intermediate in Plato´s dialogues, especially Theaetetus and Symposium. In the first section, I investigate previously in Theaetetus the notion of to metaxy as the result of mixture between percipient and perceived, by which the realm of phenomenon can be explained by the third genre, identified as to metaxy, born from a certain kind of dynamis. In the second section, I examine the mentioned notion s Symposium, expressed by Diotima of Mantineia on her encomium of Eros as daimon. My purpose in this last section is to demonstrate that the apprehension of Form of Beauty itself requires a new hermeneutic approach, which I call cultual hermeneutic, by which Plato conceives an inherent link between mythical and rational conceptions of Ideas.